Effects of Some Insecticides on Agonoscena pistaciae Burckhardt & Lauterer (Hemiptera: Psyllidae) - Adnan Tusun; Çağlar Kalkan; Serdar Satar (Turkish Journal of Agriculture: Food Science and Technology)
Chemical control is the most common method used to control Agonoscena pistaciae Burckhardt & Lauterer (Hemiptera: Psyllidae). This study compared the application of the five most widely used insecticides in the management of A. pistaciae which has resulted in significant yield losses, in Siirt (Kurtalan) and Şanlıurfa (Birecik) in 2023. Active ingredients spinetoram, lambda-cyhalothrin, deltamethrin, sulfoxaflor, and spirotetramat were examined in the study. The study was designed with four replications, and its characters were formed by the insecticides registered concentration and the control. The plots measured 3 x 3 = 9 trees. Nymph and adult counts were conducted from the middle trees before, as well as 7, 14, and 21 days after application following the application of the spray. The Henderson-Tilton formula was used to analyze the counting data for nymph or adult counts in each plot of leaf samples. All registered active ingredients effected the A. pistaciae above %80 all count days. Among the active ingredients the biological efficacy of spirotetramat was the highest compared to other insecticides. These active ingredients can be used to control A. pistaciae, with consideration given to the pest's potential resistance to insecticides and the impact of the ingredients on natural enemies.